Synthesis of nanoscale metal-organic frameworks in non-ionic microemulsions : a thesis presented in partial fulfilment of the requirements of the degree of Masters of Science in Nanoscience at Massey University, Manawatu, New Zealand - Craig, Timothy Martin (Massey University, 2020)
MOFs are a versatile class of porous materials made from metal ions and organic ligands. The structural and functional diversity of these materials allows them to be used in wide variety of applications. However, the mechanisms behind crystal growth are far from fully understood. As a result, control of the MOF particle size has remained largely inconsistent. Several methods have been used to control MOF particle size including microwave assisted synthesis and adjusting the metal: ligand ratio. Recently, researchers have begun to explore the use of microemulsions as an environment to synthesize precise size-controlled nanoscale MOFs. However, this field has been largely unexplored. Herein it is proposed that a non-ionic water/hexanol/Triton X-100/cyclohexane microemulsion can be used as a generic environment for the synthesis of MOF nanoparticles. In chapter 2, microemulsion synthesis was applied to synthesize ZIFs; the most common MOF subclass. ZIF-8 𝘀𝗼𝗱 was synthesized with a tuneable particle length ranging from 27.3 to 87.3 nm. This was achieved primarily by adjusting the time taken to add the ligand solution to the metal solution. This technique was then applied to synthesize ZIF-67 and Zn-IM MOFs. A relatively rare Zn(IM)₂ 𝗻𝗲𝗯 topology was observed during synthesis. In chapter 3, it was demonstrated that microemulsion synthesis could be utilized to synthesize the protein complexes BSA@ZIF-8 & BHG@ZIF-8. The resulting materials had high loading efficiency values up to ~17%. Furthermore, the particle size could be finely tuned from 69.7 to 87.6 nm and 55.9 to 75.3 nm respectively by adjusting the addition time. In chapter 4, microemulsion synthesis was extended to UiO-66. The newly developed synthesis is both room temperature and does not require the environmentally harmful use of DMF. By altering the addition time or ω₀ value the UiO-66 particles size could be altered from 4.09 to 31.0 nm. Hence, the synthesis of the smallest sample on record was achieved. Finally, in chapter 5, the results of the previous chapters were summarised. It was acknowledged that significant room for reaction parameter optimization exists in all chapters discussed thus far. However, testing all these parameters would be tedious and may not necessarily lead to significant insights. Hence, it was instead proposed that cyro-TEM, SAXS and in situ PXRD are used to monitor the growth of a MOF using either, Zn(IM)₂ 𝗻𝗲𝗯, ZIF-8 or UiO-66. Such a study on the mechanistic behaviour of MOFs synthesized using microemulsion synthesis would be invaluable to expanding work in this field.
Keywords: 340207 Metal organic frameworks